Regional economic disproportions and sustainability of regional economic systems under the 2022 sanctions - S. Ye. Afonin; V. S. Osipov (Управление)
In the current economic and political environment, the primary task is to strive for technological independence and self-sufficiency of the economy with maximum reliance on its own resources in development, while not excluding economic expansion by increasing competitiveness of the economy in global market. The key competitive factor is innovativeness of products and services, as well as the degree of the most advanced production technologies implementation, which together have a decisive impact on the economy efficiency in both external and domestic markets. The widespread development of globalization trends, digitalization, modern means of communication, the territorial factor importance are replaced by the factors of technological, scientific, and innovative development. In this regard, it is an urgent task to study these processes and search for factors affecting the qualitative growth of processes and manufactured products efficiency. In the present study, using mathematical and statistical methods, it has been established that the decisive value for the economy efficiency on a national scale is the value of expenditures on research and development and experimental-construction works. This indicator has a direct impact on innovation processes both in the country as a whole and in individual regions. However, one of the significant obstacles in development and sustainability of regional economies is hyperconcentration of scientific expenditures in a few regions that has a negative impact on regional development efficiency.